2007
DOI: 10.1039/b611920d
|View full text |Cite
|
Sign up to set email alerts
|

In vitro continuous amperometric monitoring of 5-hydroxytryptamine release from enterochromaffin cells of the guinea pig ileum

Abstract: A diamond microelectrode was used to sensitively, reproducibly and stably record overflow of 5-hydroxytryptamine (5-HT, serotonin) from enterochromaffin cells (EC) of the intenstinal mucosal layer. 5-HT is an important neurotransmitter and paracrine signalling molecule in the gastrointestinal tract. The diamond microelectrode was formed by overcoating a sharpened 76 microm diameter Pt wire with a thin layer of conducting diamond. After insulation with polypropylene, the conically-shaped microelectrode had a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
153
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 105 publications
(162 citation statements)
references
References 25 publications
9
153
0
Order By: Relevance
“…Diamond microelectrodes are resistant to fouling enabling these electrodes to be used for extended periods of time for sensitive and reproducible measurement of 5-HT release from the intestine. 17 Previous work showed that currents caused by oxidation of 5-HT at the electrode tip can be discriminated from oxidation currents produced by other molecules in the mucosa. 14,17 Using diamond microelectrodes, this can be accomplished by setting the voltage at the electrode tip to 0.8 V. When diamond microelectrodes are positioned near the mucosal surface, there is an abrupt increase in the oxidation current.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diamond microelectrodes are resistant to fouling enabling these electrodes to be used for extended periods of time for sensitive and reproducible measurement of 5-HT release from the intestine. 17 Previous work showed that currents caused by oxidation of 5-HT at the electrode tip can be discriminated from oxidation currents produced by other molecules in the mucosa. 14,17 Using diamond microelectrodes, this can be accomplished by setting the voltage at the electrode tip to 0.8 V. When diamond microelectrodes are positioned near the mucosal surface, there is an abrupt increase in the oxidation current.…”
Section: Discussionmentioning
confidence: 99%
“…15, 16 We showed recently that diamond microelectrodes are resistant to fouling and can be used for sensitive and stable measurement of 5-HT in the intestinal mucosa in vitro. 17 In the present study we used diamond microelectrodes to compare 5-HT disposition in the small intestinal mucosa of neonatal and adult guinea pigs. As there were marked differences in 5-HT handling between these groups of animals, we also used chromatographic, immunohistochemical, and Western blot techniques to probe the mechanisms underlying differences in 5-HT handling by the intestinal mucosa of neonatal and adult guinea pigs.…”
mentioning
confidence: 99%
“…Traditionally these recordings have been carried out on carbon fibre electrodes [9][10][11]; however boron-doped diamond [7,12] and carbon nanotube electrodes [13,14] have recently been shown to overcome electrode fouling from oxidative by-products. However limited insight is given on the influence of the 3 background matrix towards the stability and sensitivity of 5-HT measurements during these studies.…”
Section: Introductionmentioning
confidence: 99%
“…These two oxidation peaks have also be observed in other animal models, such as CD1 female mice, guinea pigs, and rabbits, where responses were attributed to serotonin and MEL. 27,29,30 Another electroactive Figure 1. Electrochemical determination of melatonin release from distal colon mucosa.…”
Section: ■ Results and Discussionmentioning
confidence: 99%